2014
DOI: 10.1016/j.ijrmhm.2014.06.003
|View full text |Cite|
|
Sign up to set email alerts
|

Impact fatigue fracture of polycrystalline diamond compact (PDC) cutters and the effect of microstructure

Abstract: Impact fatigue fracture of polycrystalline diamond compact (PDC) cutters and the effect of microstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Kanyanta et al [69] studied the impact fatigue of PDC, and showed that grain size could influence the fatigue behavior, with larger grain-size grades offering greater fatigue resistance. They developed an in-house cyclic impact test facility and compared the impact behavior of two grades of PDC of different grain sizes (mean grain sizes of 6 and 30 µm).…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanyanta et al [69] studied the impact fatigue of PDC, and showed that grain size could influence the fatigue behavior, with larger grain-size grades offering greater fatigue resistance. They developed an in-house cyclic impact test facility and compared the impact behavior of two grades of PDC of different grain sizes (mean grain sizes of 6 and 30 µm).…”
Section: Impactmentioning
confidence: 99%
“…The repeated impacts of the cutter on the rock can cause the initiation of microscopic fatigue cracks, the propagation of which can result in the chipping and spalling of fragments from the cutter. Kanyanta et al [69] studied the impact fatigue of PDC, and showed that grain size could influence the fatigue behavior, with larger grain-size grades offering greater fatigue resistance. They developed an in-house cyclic impact test facility and compared the impact behavior of two grades of PDC of different grain sizes (mean grain sizes of 6 and 30 µm).…”
Section: Impactmentioning
confidence: 99%
“…Numerous studies have shown that cyclical loading substantially reduces the force required to fracture the diamond (Kanyanta, 2014). Monotonic loading is not completely representative of tangential forces acting on the face of a cutter in an actual drilling environment, but it is a quick and telling test.…”
Section: Face Loading Testmentioning
confidence: 99%
“…Considering fracture toughness evaluation, research has been traditionally restricted to the static regime using Brazilian disk and double torsion testing methods [4,5]. More recent work however, has adopted high rate bending tests using a drop-weight tower [6], and the dynamic impact fatigue fracture of PCD compacts has also been investigated [7]. Despite these studies, there remains a limited body of knowledge in this area compared to traditional ceramic cutting tools, and thus, the investigation of the dynamic fracture toughness of PCD is vital for the evaluation and design of improved material grades.…”
Section: Introductionmentioning
confidence: 99%